(untitled) (Khairulummah, 2023)
The main aim of the study to examine the causal nexus in industrialization, urbanization and carbon emissions in Pakistan and used the time series data from 1990 to 2019. Based on the data behavior, an ARDL technique is used for estimation. This study originates that the energy consumption, exports, GDP, industrialization has optimistic and noteworthy effect on carbon emission. However, the urbanization has optimistic and noteworthy effect on CO2 emission. Moreover, there are exist two-way casualty between EC and CO2 emission, and UP and CO2 emission, while, One-way causation from GDP to CO2 emission, energy consumption to exports, urbanization to exports. However, no causality exists between exports and CO2 emission, industrialization and CO2, GDP and exports, industrialization and exports, Industrialization and GDP, UP and GDP, and UP and industrialization. The study recommended that the minimize energy consumption, control the emission from factories and focused on those industries like tourism which has small effect on the environment degradation. This study also suggests discouraging urbanization and promoting exports of goods which emission free.